2017
DOI: 10.1080/14397595.2016.1276512
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of modified metatarsal shortening offset osteotomy for forefoot deformity in patients with rheumatoid arthritis: Short to mid-term follow-up

Abstract: Modified metatarsal shortening offset osteotomy was recommended for RA forefoot disorders as one of the joint preservation surgeries in short- to mid-term follow-up. However, some modifications to avoid limitation of ROM in the MTP joint are required. It must be borne in mind that varus hindfoot and/or bony ankyloses in the mid-hindfoot can cause recurrence of dorsal dislocation/subluxation of the lesser toe MTP joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 18 publications
2
31
0
2
Order By: Relevance
“…This combination of techniques was most commonly used in the studies considered and achieved the best results, both in relieving pain and in enhancing functionality (p < 0.001) [19,20,40,43]. However, there is no evidence that this is more effective than arthroplasty in all the metatarsal heads (or the fist metatarsal), because according to the papers included in our analysis, the only related research conducted were case studies [18,45,46], which are considered to present low methodological quality. Moreover, these papers do not address the specific object of our investigation.…”
Section: Discussionmentioning
confidence: 98%
“…This combination of techniques was most commonly used in the studies considered and achieved the best results, both in relieving pain and in enhancing functionality (p < 0.001) [19,20,40,43]. However, there is no evidence that this is more effective than arthroplasty in all the metatarsal heads (or the fist metatarsal), because according to the papers included in our analysis, the only related research conducted were case studies [18,45,46], which are considered to present low methodological quality. Moreover, these papers do not address the specific object of our investigation.…”
Section: Discussionmentioning
confidence: 98%
“…Shortening oblique osteotomy (SOO) is a useful procedure to improve the weight-bearing distribution of the foot in patients with RA. Several types of metatarsal shortening osteotomies with MTP joint preservation have been described [ 7 12 ]. Hirao et al reported that the alignment score for the 2 nd through 5 th digits on the Japanese Society for Surgery of the Foot scale significantly improved by modified metatarsal shortening offset osteotomy from 1.2 ± 2.9 preoperatively to 11.8 ± 3.6 postoperatively in patients with RA foot [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several types of metatarsal shortening osteotomies with MTP joint preservation have been described [ 7 12 ]. Hirao et al reported that the alignment score for the 2 nd through 5 th digits on the Japanese Society for Surgery of the Foot scale significantly improved by modified metatarsal shortening offset osteotomy from 1.2 ± 2.9 preoperatively to 11.8 ± 3.6 postoperatively in patients with RA foot [ 7 ]. Nishida et al demonstrated that the deformity score for JSSF RA ankle and foot scale significantly improved from 13.8 to 21.1 [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for the joint-preserving arthroplasty, most patients (85.3%; n = 29/34) were treated by the combination of modified Scarf osteotomy of the hallux with the medial longitudinal approach [ 23 ] and off-set shortening osteotomy of the lesser toes with a dorsal longitudinal approach between the second and third toe MTP joint, and between the fourth and fifth toe MTP joint, as previously described [ 24 ]. The hallux was internally fixed with AcuTwist Acutrak 2.0-mm headless compression screws (Acumed USA, Hillsboro, OR) or 2.0–3.0-mm cannulated cortical screws.…”
Section: Methodsmentioning
confidence: 99%